Astrocytes Protect Neurons in the Hippocampal CA3 Against Ischemia by Suppressing the Intracellular Ca2+ Overload - Sun, Chuanqi; Fukushi, Yasuko; Wang, Yong; Yamamoto, Seiji (Frontiers in Cellular Neuroscience, 2018)
In the hippocampus, delayed neuronal death is normally seen in neurons of the CA1 region but not in those of the CA3 region. Astrocytes have been reported to play multiple supporting or pathological roles in neuronal functioning. While evidence indicates that astrocytes could exert neuroprotective effects following ischemia, the possible underlying mechanisms remain unclear. We aimed to investigate the roles of astrocytes in the process of delayed neuronal death following transient forebrain ischemia. L-α-aminoadipic acid (L-α-AAA), an astrocyte-selective gliotoxin, was injected into the hippocampal CA3 region of rats through a cranial window to selectively damage astrocytes. Immunofluorescence staining of glial fibrillary acidic protein was used to evaluate the effect of L-α-AAA on astrocyte numbers. Three days after the L-α-AAA injection, transient forebrain ischemia was induced by a modification of the four-vessel occlusion procedure. Seven days after transient forebrain ischemia, hematoxylin-eosin staining was performed to reveal the morphology of hippocampal pyramidal neurons. In rats with ischemia and reperfusion, regional cerebral blood flow (rCBF) and change in intracellular Ca2+ concentration ([Ca2+]i) were separately measured in CA1 and CA3 regions. L-α-AAA injection significantly decreased the number of astrocytes in CA3, but did not affect the pattern of rCBF changes upon ischemia/reperfusion. Seven days after transient forebrain ischemia, in rats receiving L-α-AAA, delayed neuronal death comparable with that in CA1 was observed in the CA3 region. In addition, the pattern of increase in [Ca2+]i due to transient forebrain ischemia was completely changed in the hippocampal CA3. The loss of astrocytes induced a persistent increase in [Ca2+]i in the CA3 region following transient ischemia, similar to what is observed in the CA1 region. Our study indicates that astrocytes in the hippocampal CA3 region exert neuroprotective effects following transient forebrain ischemia and act by suppressing the intracellular Ca2+ overload. Furthermore, our study will most likely provide a new therapeutic strategy for brain ischemic diseases, targeted to astrocytes.